Analisis Faktor-Faktor Yang Mempengaruhi Ketimpangan Pendapatan: Analysis of Factors Influencing Income Inequality - Ahmad Fauzan Burhan; Basri Bado; Abdul Rajab; Sri Astuty; Irwandi (Universitas Sumatera Barat, 2025)
Economic development issues are unavoidable for any country, including Indonesia, particularly in the Province of South Sulawesi. One persistent challenge is income inequality. This phenomenon occurs at various levels, including disparities between urban and rural areas, across regencies/municipalities, and among regions within South Sulawesi. Such inequality reflects a gap in income distribution that must be addressed seriously to achieve more inclusive and equitable regional development. This study aims to analyze the effects of economic growth, unemployment rate, and Human Development Index (HDI) on income inequality in South Sulawesi Province during the period 2014–2023. The method employed is panel data regression analysis, combining cross-sectional data from 24 regencies/municipalities and time series data over ten years. Data processing was carried out using EViews 12. The findings reveal that economic growth and unemployment rate variables have a negative but statistically insignificant relationship with income inequality. Conversely, the Human Development Index has a statistically significant negative effect, with a p-value of 0.0000, on income disparity in the region.